A Theory of the Classifications of Thailand’s Installation Art by Mark Rosenthal - Sodamak, Chutima (Journal of Fine and Applied Arts Khon Kaen University, 2021)
Thai artists’ creations have been continuously developed through an individual’s technique and the use of materials or media, resulting in a variety of expressions. The roots of installation art lie in the conceptual art and the art form is well-received by Thai contemporary artists. However, there is no clear classification of art installations by Thai artists. Therefore, this study aims to propose the theory by Mark Rosenthal as an easy criterion to classify art installations by Thai artists. Rosenthal proposes two broadly defined types of installation which are 1. Filled-Space Installation, an installation that is modified or created to fill the empty space, is divided further into “enchantments” and “Impersonations” and 2. Site-Specific Installation, an installation using the site specifically, is divided further into “Interventions” and “Rapprochements”. The researcher uses this theory to classify four artworks by four Thai artists, “Shed the Shells”, 2003, by Phatyos Buddhacharoen, “Dilemma”, 2000, by Kamol Paosawat, “History Class”, 2000, by Sutee Kunavichayanon, and “Window of Rethinking: Homage to Karhil Gibran”, 1998, by Nipan Oranniwesna. The researcher found that the theory is considered inadequate to cover all art installations by Thai artists as Thai contemporary artists combined different types of artistic expressions to create their artworks, for example, art installation with performance art, art installation with interactive art, or art installation with mixed media. Thus, the paper aims to explain the theory to students and the general public for an increased understanding of art installation by using only examples of site-specific installations by Thai artists. Moreover, the theory can be used to study any art installations in the future.